Methods of analysis for functional foods and nutraceuticals (CRC Press, 2002)
This book provides a central resource and available reference for the analysis of well-known functional food components, such as carbohydrates, lipids, and vitamins, and a unique resource for descriptions of the analytical methodology for non-nutrition food ingredients.